Translation and Validation of the Persian Version of the Wisconsin Stone Quality of Life Questionnaire - Hoseinbeigi, Mohammad Soroush; Shakiba, Behnam; Faegh, Ali; Soleimani, Sevim; Maghsoudi, Robab (Urology Journal, 2024)
Purpose: Patients with kidney stones have a lower quality of life (QOL) than healthy patients; however, treatment guidelines neglect their QOL. Wisconsin stone QOL test (WIS-QOL) is the first specific questionnaire for urolithiasis patients. This study evaluated the reliability and validity of the translated Persian version of the WIS-QOL questionnaire in patients with kidney stones. Material and methods: All patients (> 18 years old) with a history of urolithiasis were included in this cross-sectional. The WIS-QOL questionnaire was translated depending on Hutchinson’s guideline. Effects of urolithiasis on the patient’s social activity, emotions, disease, and vitality were evaluated. Pearson Correlation and Cronbach’s alpha test were used to assess the validity and reliability of the questionnaire. All data were analyzed by SPSS software version 26.0. Results: Among 154 urolithiasis patients, 94 (61%) were males, and 60 (39%) were females. The mean age was 50.4 years (SD: ± 13.6), and the mean QOL score was 84.7 (SD: ± 21.8). For each question, the numerical value of the Pearson Correlation Coefficient has been compared with the numerical value, and the validity of the questionnaire was confirmed. The overall Cronbach’s alpha was 0.94 for all four areas of the questionnaire, so the reliability of the questionnaire in Persian was confirmed. Conclusion: The present study showed the reliability and validity of the Persian version of the WIS-QOL questionnaire in symptomatic urolithiasis patients. The present study showed the status and impact of urolithiasis on QOL however, longitudinal and prospective studies should be done to specify changes over time.